Hungarian spirits palinka as a “hungaricum” II. The effect of tax-free production in Hungary and in the European Union - Harcsa, Imre Milán (Applied Studies in Agribusiness and Commerce, 2016)
Palinka is a traditional Hungarian fruit spirit prepared exclusively by the distillation of fruit mash or fruit pulp. As an alcohol product, it is subject to the Act CXXVII of 2003 on Excise Duties and Special Regulations on the Distribution of Excise Goods amended several times. The present government of Hungary pledged to grant the right of free palinka distillation again in the previous election campaign. As of 27 September 2010, the excise duty of subcontract-distillation was repealed, and the previously non-existent “official” home distillation was introduced, which resulted in explicit revenue losses for the state budget. The modification of the law mentions distillate instead of the word palinka. The difference between the two notions will be discussed in the present study. Presumably, lawmakers did not consider the fact that at the time of Hungary’s EU accession we entered into an agreement stipulating that the tax on subcontract-distillation should not be lower than 50% of the tax on alcohol products. Having been unable to agree on a solution to the problems in question, Brussels launched an infringement procedure against Hungary. Finally, Hungary was convicted; therefore, tax exemption or palinka distillation shall be ceased. This regulation came into force on 01 January 2015. The reactions of those who used the services of subcontract distillation were negative; turnover plunged by approximately 85% compared to the year of 2014. The present research will present the amendments concerning home distillers due from 2016 and the elements of the bill intended to amend the Act LXXIII. of 2008. JEL CODE: K34, L51, L66